Empirical Tests for the Existence of Group Utility Functions - Shapiro, Perry; Braithwait, Steven (Review of Economic Studies, 1979)
Perry Shapiro, Steven Braithwait; Empirical Tests for the Existence of Group Utility Functions, The Review of Economic Studies, Volume 46, Issue 4, 1 Octob